The Conundrum of Training and Capacity Building for People with Learning Disabilities Doing Research. Issue 6 (2nd September 2015) - Nind, Melanie; Chapman, Rohhss; Seale, Jane; Tilley, Liz
Abstract : Background: This study explores the training involved when people with learning disabilities take their place in the community as researchers. This was a theme in a recent UK seminar series where a network of researchers explored pushing the boundaries of participatory research. Method: Academics, researchers with learning disabilities, supporters and other inclusive researchers considered important themes arising from presentations about developments in participatory research. The paper emerges from critical reflection on these rich discussions. Results: A seminar series is a form of research training and capacity building, albeit a dynamic, interactive and collegial one. More formal training in research skills for people with learning disabilities is being developed but raises questions regarding the best contribution people with learning disabilities can make to the research process. Conclusion: There are various models of training for inclusive research, but these need to be reciprocal if they are not to undermine the inclusive goal.